Characteristics of measles immunity in students of the pediatric faculty of a medical university - D. O. Ivanov; V. N. Timchenko; E. B. Pavlova; E. V. Barakina; T. M. Chernova; N. V. Pavlova; O. V. Bulina; A. N. Nazarova (Журнал инфектологии)
Objective: to evaluate the intensity of measles immunity in students of I–VI courses of the pediatric faculty of St. Petersburg State Medical University.Materials and methods: titers of antibodies to measles virus were determined in 986 students of I–VI courses in May –June 2019. The level of measles antibodies was determined by enzyme-linked immunosorbent assay.Results: positive (protective) titres of measles antibodies were detected in 555 people. (56.4%), the absence of measles immunity was found in 431 people. (43.6%), including 57 people. (5.8%) specific antibodies were not detected. The relationship between the level of collective immunity and the duration of the period after the last vaccination against measles was revealed.Conclusions: in the majority of examined students (96.2%), protective titers of measles antibodies remained for 10 years after the last vaccination. Subsequently, a significant decrease in the level of measles antibodies was noted. All students who do not have a protective IgG titer are shown measles vaccination with live measles vaccine in accordance with the instructions for use.